Biomarkers for physical frailty and sarcopenia: state of the science and future developments. Issue 4 (7th July 2015) - Calvani, Riccardo; Marini, Federico; Cesari, Matteo; Tosato, Matteo; Anker, Stefan D.; von Haehling, Stephan; Miller, Ram R.; Bernabei, Roberto; Landi, Francesco; Marzetti, Emanuele; ,
Abstract: Physical frailty and sarcopenia are two common and largely overlapping geriatric conditions upstream of the disabling cascade. The lack of a unique operational definition for physical frailty and sarcopenia and the complex underlying pathophysiology make the development of biomarkers for these conditions extremely challenging. Indeed, the current definitional ambiguities of physical frailty and sarcopenia, together with their heterogeneous clinical manifestations, impact the accuracy, specificity, and sensitivity of individual biomarkers proposed so far. In this review, the current state of the art in the development of biomarkers for physical frailty and sarcopenia is presented. A novel approach for biomarker identification and validation is also introduced that moves from the 'one fits all' paradigm to a multivariate methodology.